The Sustainable Harvesting of Edible Insects in South Africa, with Reference toI ndigenous Knowledge, African Science, Western Science and Education - Toms, Rob (The Australian Journal of Indigenous Education, 2007)
Abstract In our ongoing research on edible insects in the Limpopo Province of South Africa, we have found evidence of the unsustainable harvesting of edible insects and the food plants of certain insects. The decline in the edible insect industry, together with the need for food security provides a strong incentive to investigate possible causes of problems using different knowledge systems. Any solution to these problems needs to take Indigenous Knowledge Systems (IKS) into account if it hopes to be successful and sustainable. We have found that different communities have different explanations for the same phenomena. Some of these explanations correspond with the explanations for the same phenomena in Western science. Where areas of overlap between IKS and Western science exist, these can be used in education in such a way that recommendations for sustainable harvesting can be developed with reference to African science. In this process, the area of overlap between the systems may grow as information from one system is incorporated in another. In this contribution the overlapping roles of IKS, African science and Western science are explored in the teaching of the sustainable harvesting of Indigenous resources for food security and conservation. This creates opportunities to teach relevant science in such a way that the concerned communities can benefit through better food security and the conservation of culturally important plants and animals.